Antimicrobial effect of coconut oil on Staphylococcus aureus: an implication of Staphylococcus epidermidis induced fermentation - Mahaklan, Lalita; Pratuangdejkul, Jaturong; Satitpatipan, Veena (Life Sciences, Medicine and Biomedicine, 2022)
Staphylococcus epidermidis is a commensal bacterium of human skin. S. epidermidis possesses lipolytic activity to digest skin surface lipids into the smallest unit of fatty acids (FAs). Most FAs hold antimicrobial properties essential for protecting skin from invading microorganisms. In this study, we were interested in virgin coconut oil (VCO), the source of several medium-chain fatty acids (MCFAs) such as lauric acid and caprylic acid. Those MCFAs products demonstrated remarkable antibacterial activity. Our results showed that crude supernatant from the culture medium of S. epidermidis with VCO fermentation exhibited the growth inhibition effect on Staphylococcus aureus. This bacterium causes a wide range of skin diseases. A co-culture of S. epidermidis and S. aureus in a rich medium with 2.5% (v/v) VCO significantly reduced the growth of S. aureus compared to those without VCO (p-value